گہگیری لبزانک: Rebellious Literature - Hakeem, Tahir (Hanken, 2015)
Life is the subject matter of literature. Resistance is the part of human life, poets, writers and intellectuals take up resistance theme as the subject matter of their poetry and others literary genre. This paper deals with the begining of resistance, its aim and the role of resistance. The article is also discussed the impact of resistance literature and the role of poet and writer creating such kind of literature which bring about a social change.